IMPLEMENTASI KEBIJAKAN TUKAR MENUKAR ASET DESA BERUPA TANAH DI KABUPATEN KENDAL (Studi Implementasi Permendagri Nomor 1 Tahun 2016 tentang Pengelolaan Aset Desa) - Rusliana Rusliana; Sri Kusriyah (UNISSULA Semarang, 2018)
The village treasury is one of the village's assets / wealth which is highly expected to support the wheels of village government. As one source of village income and income of village apparatus, village cash lands should be productive land. With the existence of Law No. 6 of 2014, related to the management of property owned by the village has changed that is with the enactment of the Minister of Home Affairs Regulation No. 1 of 2016 on the Management of Village Assets, which provides an opportunity for the village to be able to implement the transfer of village assets in the form of land through exchange, not only to be used for the public interest, but also not for the public interest, and the village cash lands in addition to the public interest and not for the public interest.However, in fact Permendagri Number 1 Year 2016 which serve as a legal basis for the exchange of assets of villages in the form of land can not be fully implemented. This is because the substance / material in Permendagri still need to be examined again, among others, the unclear formulation and legal uncertainty of Permendagri No. 1 of 2016.Keywords : Swap Exchange, Village Cash Land, Village Asset in the form of Land, and Permendagri Number 1 Year 2016.